Priority areas for Bangladesh: Roadmap to 2041 as Developed Country - Husain, Taha; Kamruzzaman, Dr. (Archives of Community Medicine and Public Health, 2020)
Vision 2041, which is a continuation of vision 2021, has been embraced by the government of Bangladesh and aims to carry the country to the path of development Bangabandu dreamed of. The government of Bangladesh has already introduced the 2021-2041 Perspective Plan (PP2041). The key aim of Vision 2041 is to eradicate extreme poverty, achieve the Upper Middle Class by 2030 and the status of a high economic nation by 2041. This study aiming to find out the major priorities area to be developed country by 2041 and achieve vision 2041. This study based on the secondary data of different scholars finds some major areas that must be improved as soon as possible. Priorities area are modern power grid, Blue economy, skill development, recognition of free lancing and urban development. Those areas will boost up the country to be developed country with the fix time frame.